Study forBuddhism of Tai Lue CultureInJinghong city, XishuangbannaProvince, People’s Republic ofChina - Li, Dao (Journal of Fine and Applied Arts Khon Kaen University, 2018)
Around the 3rd century, buddhism came to Jinghongcity.And the 12th century, Buddhism reached its most prosperous inJinghongcity.Current conditions and problemsBuddhism of Tai culture in Lue culturein Jinghong city,the role and importance of Buddhism declined.Middle-aged and elderly people are still strict in Buddhism and philanthropy.The teenagers and young people less.The first problem is that there are no priests and seminarians who will inherit the blessings of Buddhism.Another problem is that no one will inherit Buddhism.Among the factors that affect Buddhism of Tai Lue culture change, In Jinghong city,XishuangbannaProvince, People’s Republic ofChina,the most is politics and state policy.For example, during the Cultural Revolution of China,Prohibition of faith Buddhism. The least factors that affect is technology. The Tai Lue people are more interested in learning technology than Buddhism.